The Influence of Talent Management and Organizational Culture on Employee Performance at Telkomcel Timor-Leste - Santos Piedade, Joaninha Dos; Dudija, Nidya (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
In the era of globalization and increasingly intense business competition, improving employee performance has become a crucial factor for organizational success. This study aims to analyze the influence of Talent Management and Organizational Culture on employee performance at Telkomcel Timor Leste. Using a quantitative method, data were collected through questionnaires distributed to 135 respondents and analyzed using SPSS. The results indicate that Talent Management has a positive and significant effect on employee performance, with a regression coefficient of 0.539 and a significance value of 0.000, explaining 71.9% of the performance variation. Organizational Culture also contributes significantly, with a regression coefficient of 0.186 and a significance value of 0.007, explaining 66.8% of the performance variation. Simultaneously, these two variables explain 72.7% of the variation in employee performance, with an F-value of 176.118 (p = 0.000). This study confirms that effective talent management and a strong organizational culture are dominant factors in enhancing employee performance at Telkomcel Timor Leste. The findings provide strategic recommendations for the company to optimize human resource management to achieve optimal performance.